All Days 2013
DOI: 10.2118/166033-ms
|View full text |Cite
|
Sign up to set email alerts
|

Using Near Wellbore Upscaling to Improve Reservoir Characterization and Simulation in Highly Heterogeneous Carbonate Reservoirs

Abstract: Carbonate reservoirs host a major portion of the world's remaining conventional and unconventional hydrocarbon reserves, typically containing multi-scale geological heterogeneities varying over many orders of magnitude in size. Characterizing and representing them robustly in reservoir models is a prime challenge in carbonate reservoir simulation. One of the key aims of this paper is, hence, to present a novel near wellbore upscaling (NWU) workflow that addresses the challenges associated with conventional car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The k z /k x ratio is typically assumed to be 0.1. However, several studies on sandstones (Jones et al 1987;Hanks et al 2011;Baker et al, 2005) and carbonates (Chandra et al 2013;Sun et al 2017;Dernaika et al 2018), including the work presented here, showed the occurrences where k z > k x . The underlying geological causes should be well understood for reliable geomodels and multiphase flow simulations.…”
Section: Introductionmentioning
confidence: 46%
See 2 more Smart Citations
“…The k z /k x ratio is typically assumed to be 0.1. However, several studies on sandstones (Jones et al 1987;Hanks et al 2011;Baker et al, 2005) and carbonates (Chandra et al 2013;Sun et al 2017;Dernaika et al 2018), including the work presented here, showed the occurrences where k z > k x . The underlying geological causes should be well understood for reliable geomodels and multiphase flow simulations.…”
Section: Introductionmentioning
confidence: 46%
“…Unlike clastics, carbonates appear to show weaker k z /k x trends with scale, perhaps decreasing by 1 or 2 orders of magnitude from the core-to large-scale (e.g., Wang et al 1994;Chandra et al 2013;Pamungkas et al 2020). This smaller change than sandstones may be partly resulting from better core-scale sampling because carbonates tend to be well consolidated, have good core recoveries, and are exhaustively measured (in the vertical direction) when using whole-core samples.…”
Section: Geological and Geostatistical Analysis Results Statistical A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Carbonate reservoirs host about 70% of the conventional oil reserves in the Middle East, and most of them are naturally fractured [4]. The Naturally Fractured Carbonate Reservoirs (NFCR) are well known for their low recoveries [5,6] compared to the clastic reservoirs due to the multiscale of geological heterogeneities, [5,7,8]. Therefore, accurate modelling of reservoir heterogeneities is a critical and an essential stage for further improvements in the modelling and simulation process, which enhance historical matching or future prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the measurement scales of core analysis, wireline logs, and pressure transient analysis vary from a few microns to several metres (Barnett et al, 2013). However, most of these measurement scales are different from the scale that is used in reservoir simulation and analysis, which is of the order of metres 55 vertically and tens to hundreds of metres laterally.…”
mentioning
confidence: 99%